The effects of Borrelia infection on its wintering rodent host - Sipari Saana; Hytönen Jukka; Pietikäinen Annukka; Mappes Tapio; Kallio Eva R (Germany, 2022)
In seasonal environments, appropriate adaptations are crucial for organisms to maximize their fitness. For instance, in many species, the immune function has been noticed to decrease during winter, which is assumed to be an adaptation to the season's limited food availability. Consequences of an infection on the health and survival of the host organism could thus be more severe in winter than in summer. Here, we experimentally investigated the effect of a zoonotic, endemic pathogen, Borrelia afzelii infection on the survival and body condition in its host, the bank vole (Myodes glareolus), during late autumn-early winter under semi-natural field conditions in 11 large outdoor enclosures. To test the interaction of Borrelia infection and energetic condition, four populations received supplementary nutrition, while remaining seven populations exploited only natural food sources. Supplementary food during winter increased the body mass independent of the infection status, however, Borrelia afzelii infection did not cause severe increase in the host mortality or affect the host body condition in the late autumn-early winter. While our study suggests that no severe effects are caused by B. afzelii infection on bank vole, further studies are warranted to identify any potentially smaller effects the pathogen may cause on the host fitness over the period of whole winter.